2000
DOI: 10.1017/s0950268800004830
|View full text |Cite
|
Sign up to set email alerts
|

Population-based surveillance for bacterial meningitis in the Dominican Republic: implications for control by vaccination

Abstract: Quantifying the local burden of disease is an important step towards the introduction of new vaccines, such as Haemophilus influenzae type b (Hib) conjugate vaccine. We adapted a generic protocol developed by the World Health Organization for population-based surveillance of bacterial meningitis. All hospitals that admit paediatric patients with meningitis in the National District, Dominican Republic were included in the system and standard laboratory methods were used. The system identified 111 cases of confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…The National District-including the capital, Santo Domingo, and the surrounding periurban area-accounts for approximately 40% of the country's population, with 300 000 children less than 5 years of age. In 1998 and 1999, active, population-based surveillance for bacterial meningitis in eight hospitals (four public and four private) in the National District documented an incidence of 13 cases of Hib meningitis per 100 000 children less than 5 years of age (11). During this 2-year period, surveillance officers regularly reviewed laboratory records and admission logs to identify case patients and completed standardized case report forms.…”
Section: Surveillance For Bacterial Meningitismentioning
confidence: 99%
See 1 more Smart Citation
“…The National District-including the capital, Santo Domingo, and the surrounding periurban area-accounts for approximately 40% of the country's population, with 300 000 children less than 5 years of age. In 1998 and 1999, active, population-based surveillance for bacterial meningitis in eight hospitals (four public and four private) in the National District documented an incidence of 13 cases of Hib meningitis per 100 000 children less than 5 years of age (11). During this 2-year period, surveillance officers regularly reviewed laboratory records and admission logs to identify case patients and completed standardized case report forms.…”
Section: Surveillance For Bacterial Meningitismentioning
confidence: 99%
“…The objective of this study was to evaluate the impact of routine childhood immunization against Hib on both confirmed and probable cases of bacterial meningitis in the Dominican Republic, where bacterial meningitis has been a reportable disease since 1998 (10). Before the introduction of Hib conjugate vaccines into the routine infant immunization schedule in 2001, Hib was the leading cause of bacterial meningitis in children after the first month of life (11). This report summarizes trends in confirmed and probable cases of bacterial meningitis among children admitted to the main pediatric referral hospital in Santo Do-mingo from 1998 through 2004 and presents the results of a case-control study of the effectiveness of Hib vaccine against culture-confirmed disease.…”
mentioning
confidence: 99%
“…Eight studies of meningitis 23,31,35,37,47,52,54,57 (Fig. 2) and 5 of bacteremia 28,54,55,57,61 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The pooled CFR in the age group between 0 and 59 months was 33.2 (CI 95% 21.3-46.2) for meningitis [37][38][39]43,46,55,61 . The CFRs ranged from 12% in Trotman 2009 38 to 60% in Reis et al 35 The sensitivity analysis excluding Reis et al 35 showed a pooled CFR of 29.3% (95% CI: 19.9-39.7).…”
Section: Resultsmentioning
confidence: 99%
“…Before 2003, when support from PneumoADIP commenced, few GAVI-eligible countries (countries with gross national income per capita !US$1000) conducted pneumococcal disease surveillance. In addition, data collected in different countries could not be compared or aggregated, because of heterogeneity in case ascertainment, evaluation, and enrollment methods [4,[9][10][11][12][13]. Consequently, it was difficult to attribute observed inter-or intracountry differences in pneumococcal disease epidemiology to true epidemiological differences, rather than methodological differences [14].…”
mentioning
confidence: 99%